The identities of Catherine de' Medici - Broomhall, Susan (Leiden ; Boston : Brill, 2021)
"In The Identities of Catherine de' Medici Susan Broomhall provides an innovative analysis of the representational strategies that constructed Catherine de' Medici, and sought to explain her behaviour and motivations. Through her detailed exploration of the identities that the queen, her allies, supporters, and clients sought to project, and how contemporaries responded to them, Broomhall establishes a new vision of this important sixteenth-century protagonist, a clearer understanding of the dialogic and dynamic nature of identity construction and reception, and its consequences for Catherine de' Medici's legacy, memory and historiography"--
Heir : the Medici legacy -- Partner : the king's representative -- Mother : raising son-kings -- Friend and ally : nurturing daughter-queens -- Chief mourner of the Valois : the exclusivity of intimacy -- Carer : production and investment as protection of France -- Murderer : histories of violent emotions -- Spiritual sister : the community of Le murate.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 03, 2021).
eBooks on EBSCOhost
Keywords: Catherine de Médicis, -- Queen, consort of Henry II, King of France, -- 1519-1589.; Catherine de Médicis, -- Queen, consort of Henry II, King of France, -- 1519-1589 -- Psychology; Catherine de Médicis, -- Queen, consort of Henry II, King of France, -- 1519-1589; Queens -- France -- Biography; Queens -- France -- Historiography; Women -- Political activity -- France -- History -- 16th century; Sex role -- Political aspects -- France -- History -- 16th century; Political culture -- France -- History -- 16th century; France -- Politics and government -- 16th century; France -- History -- 16th century; Reines -- France -- Biographies; Reines -- France -- Historiographie; Femmes -- Activité politique -- France -- Histoire -- 16e siècle.; Rôle selon le sexe -- Aspect politique -- France -- Histoire -- 16e siècle.; France -- Politique et gouvernement -- 16e siècle.; France -- Histoire -- 16e siècle.; Political culture; Politics and government; Psychology; Queens; Sex role -- Political aspects; Women -- Political activity; France; 1500-1599; Biographies; History